2022
DOI: 10.1101/2022.03.10.483831
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRISPR-Cas12a targeting of ssDNA plays no detectable role in immunity

Abstract: CRISPR-Cas12a (Cpf1) is a bacterial RNA-guided nuclease that cuts double-stranded DNA (dsDNA) at sites specified by a CRISPR RNA (crRNA) guide. Additional activities have been ascribed to this enzyme in vitro: site-specific (cis) single-stranded DNA (ssDNA) cleavage and indiscriminate (trans) degradation of ssDNA, RNA, and dsDNA after activation by a complementary target. The ability of Cas12a to cleave nucleic acids indiscriminately has been harnessed for many applications, including diagnostics, but it remai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…For invader defense, one ramification of the target expression threshold is that an anti-CRISPR protein (Acr) (Bondy-Denomy et al, 2013;Marino et al, 2020) that reduces the concentration of activated Cas13a complexes could rapidly interfere with the immune response. Accordingly, recent work reporting an Acr against Cas13a showed that the invading Acr-encoding phage could shut down CRISPR defenses and proliferate in the first wave of infection (Meeske et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For invader defense, one ramification of the target expression threshold is that an anti-CRISPR protein (Acr) (Bondy-Denomy et al, 2013;Marino et al, 2020) that reduces the concentration of activated Cas13a complexes could rapidly interfere with the immune response. Accordingly, recent work reporting an Acr against Cas13a showed that the invading Acr-encoding phage could shut down CRISPR defenses and proliferate in the first wave of infection (Meeske et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sybr-gold staining revealed that even though the extended single-stranded 3’ end of the target RNA was trimmed, the target RNA otherwise remained intact and was protected from degradation with a molar equivalence or excess of Cas12a2. This is distinct from the cleavage mechanisms of other Cas12 nucleases that achieve antiphage immunity through cleavage in cis 15,27 , and is reminiscent of Cas13 RNase activity in cis and trans , where the hybridized region of the target RNA remains intact 16,17 .…”
Section: Resultsmentioning
confidence: 93%
“…This is in stark contrast to the highly accessible Cas12a2 RuvC active site in the ternary complex, providing a structural basis for efficient cleavage of a wide range of substrates in trans . The lack of a Nuc domain and the presence of a highly exposed RuvC active site in the ternary structure thus explain why Cas12a2 collateral nuclease activation results in an Abi phenotype (Dmytrenko 2022) while Cas12a collateral ssDNase activity does not play a role in bacterial immunity 27 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that CRISPR-mediated DNase activity may also cause Abi through indiscriminate dsDNases (e.g., NucC) activated by type III system secondary messengers 12, 13 , or indiscriminate ssDNase activity from type V Cas12a effectors 14 . However, type III CRISPR-mediated dsDNase activity has yet to be examined in vivo , and the ssDNase activity of Cas12a has not been shown to cause Abi 15 .…”
Section: Main Textmentioning
confidence: 99%